Legal Study Concerning Zero Verdicts Related to the Principles of Certainty, Justice and Benefits in Indonesia - Fauzia Awaludin; Rehnalemken Ginting (International Journal of Law, Crime and Justice, 2024)
A nil sentence is very appropriate to apply to defendants whose verdict is sentenced to death, such as in the case of Muhammad Natsir and Heru Hidayat. However, the Dimas Kanjeng case certainly raises a different problem, where the panel of judges imposed a maximum prison sentence of 20 years, so if there are other cases the verdict must be nil. This means that the defendant, who was previously sentenced to 20 years in prison, was not increased to life imprisonment. Another problem is the lack of integrated administration between courts which results in overlapping criminal sanctions that exceed 20 years. Tstelsel's absorption in a sharpened realist concursus states that it is necessary to review the level between crimes that have permanent legal force and crimes that have just been revealed based on higher criminal threats, so that the implementation of a nil sentence achieves the principles of legal certainty, justice and expediency. The implementation of the nil sentence must be socialized to the wider community, especially in the case of Dimas Kanjeng and Muhammad Natsir, who in their decision were sentenced to a nil sentence because they had previously been sentenced to death. The aim of the outreach is to ensure that there is no misunderstanding of the defendant's release from criminal sanctions, because a zero verdict arises because the verdict has been maximum and can no longer be handed down. Judges need to interpret in more depth the basic reasons for giving a nil verdict which is linked to SEMA No. 1 of 2022 to better ensure justice and benefits for society, which of course is adjusted to the legal facts obtained during the trial period.